Variations in the concentration of subsoil gases and the atmospheric electric field prior to some earthquakes in Kamchatka - @Makarov, Evgenii O.; Akbashev, Rinat R.; Glukhov, Vitalii E. (Геосистемы переходных зон)
In Kamchatka, there are continuous networks of observation of variations in subsoil gases, the atmospheric electric field, and the Earth’s surface tilts. The aim of the study was to compare the data obtained by these networks to identify common anomalous variations prior to some strong earthquakes in Kamchatka. The article presents new information on the development of anomalous variations in the subsoil gas field and the atmospheric electric field prior to two strong earthquakes in Kamchatka: March 16, 2016, with МW = 6.6, and the Zhupanovo earthquake on January 30, 2016, with МW = 7.2. The presented data demonstrate the processes of influence of the exhalation of subsoil radon and its daughter products on the ionization balance of the surface layer of the atmosphere. A conclusion was made about the necessity of integrating various methods of recording geophysical fields, including direct measurements of crustal deformation, for the successful advancement of approaches to earthquake forecasting